Impact of Genetically Predisposed Skin Barrier Function Abnormalities on the Onset and Course of Food Allergy in Children - O.P. Pakholchuk (Zaslavsky O.Yu., 2015)
The increase in the incidence of the food allergy (FA) occurs more rapidly than changes in the genome sequence. To investigate the impact of genetically predisposed skin barrier function abnormalities associated with filaggrin (FLG) genes polymorphism on the FA onset and course, we studied 53 children with skin FA symptoms. Genotyping was performed for FLG variants R501X and 2282del4. Results. The frequency of 2 variants in the study population was 0.018 for R501X and 0.075 for 2282del4. The combined allele frequency was 0.096. All patients were heterozygotes. Children with mutations showed significant odds ratio (OR) of 31.3 (95% CI 2.1; 452.0) in terms of early onset of the skin allergy symptoms - during 1st month of life. And had no influence on the FA clinical signs start after 12 months of age (OR 0.5 (0.05; 4.85), p < 0.05). Null mutations were clinically important risk factors for the persistent transepidermal water loss (TEWL). Conclusion. Genetically predisposed skin barrier function abnormalities have impact on early FA onset and are important for persistent TEWL.